Volume 6A: Turbomachinery 2013
DOI: 10.1115/gt2013-94975
|View full text |Cite
|
Sign up to set email alerts
|

Axial-Slot Casing Treatments Improve the Efficiency of Axial Flow Compressors: Aerodynamic Effects of a Rotor Redesign

Abstract: A state-of-the-art transonic compressor rotor has a distinct potential for increased efficiency if modified for improved interaction with an axial-slot type casing treatment. Reducing the number of blades and thus the surface lowers friction losses but increases tip clearance effects and deteriorates the stall margin due to the higher aerodynamic blade loading. The latter two negative effects can be compensated for by the casing treatment, thus restoring the required stall margin and gaining an overall reducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…Casing treatment or placing a porous casing around the rotor tip is in effect a technique to control the casing boundary layers and thus delay the occurrence of the instabilities. This fact has been confirmed by several investigators [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20].…”
Section: Introductionsupporting
confidence: 69%
See 1 more Smart Citation
“…Casing treatment or placing a porous casing around the rotor tip is in effect a technique to control the casing boundary layers and thus delay the occurrence of the instabilities. This fact has been confirmed by several investigators [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20].…”
Section: Introductionsupporting
confidence: 69%
“…Results showed considerable improvement in the stall margin without efficiency penalty. In this recent development, it was shown to be possible to improve the efficiency of the transonic axial flow compressor stage with axial slots casing treatment with the rotor redesign [19]. Voges et al [20] carried out interesting measurements with bend skewed casing treatments on transonic stage at 20% axial coverage and observed that there is exchange of fluid between rotor passage and casing treatment slots due to pressure differential.…”
Section: Introductionmentioning
confidence: 99%
“…While early attempts to design CTs were based on analytic considerations and test experiences, the progress in 3D CFD and optimization techniques enables new improvement possibilities. Good examples are the published CT simulation and test results by Streit [5] and Brandstetter [6]. The effect of the herein developed and investigated CT is limited to the blade tip region and it is supposed to only act if the rotor is highly throttled close to its operation limit.…”
Section: Introductionmentioning
confidence: 97%
“…Owing to the outstanding capacity of improving the compressor stability, the emphasis is laid on the application and exploration of axial slots [3][4][5][6][7][8] and axial skew slots [9][10][11][12][13][14][15][16] in most of the slot CT investigations. Wilke and Kau 3 performed a numerical investigation of axial slot CT on a transonic axial flow compressor, where the result shows that at 88% design speed, axial slot obtains the 6.5% decrease for the stall mass flow rate with the 5% decrease for the maximum efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Wilke and Kau 3 performed a numerical investigation of axial slot CT on a transonic axial flow compressor, where the result shows that at 88% design speed, axial slot obtains the 6.5% decrease for the stall mass flow rate with the 5% decrease for the maximum efficiency. A numerical investigation by Anton Streit et al 4 on a single-stage transonic compressor with an inlet guide vane (IGV) shows that the axial slot can result in the 60% increase of the rotor mass flow working range without the efficiency loss. Emmrich et al 11 performed an experimental investigation on a singlestage subsonic compressor, and the results indicated that axial skew slots gain an approximate 50% increase of the mass flow working range with the 1.4% decrease for the efficiency of the design condition.…”
Section: Introductionmentioning
confidence: 99%